Development of canned Marikina Everlasting (Marikina meat loaf) - Estrada, Judea Mae C. (College of Home Economics, University of the Philippines Diliman, 2016)
Everlasting is a ground pork dish indigenous to Marikina City. It is cooked inside a llanera, thus it is alternatively called Llanera. When removed from the mold, the dish is quite similar to meatloaf. Since Everlasting is packaged in a llanera, the open conditions subject the food to physical, chemical, and biological hazards. Canning of Everlasting may be able to address the food hazards and packaging issues inherent to the traditional Everlasting. A standardized formulation for Everlasting was subjected to a consumer acceptance test to determine its acceptability. The thermal process schedule for the canned Everlasting was established via heat penetration studies and verification of the calculated process was done. Fifty random untrained panelists recruited from the College of Home Economics student body participated in the sensory evaluation. The nine-point Category scale was used to determine the quality attributes intensity ratings for the Everlasting, while the nine-point Hedonic scale was used to determine acceptability. The standardized formulation for Everlasting had a fairly high acceptability score of 7.06, which translates to "Like moderately". When the formulation and procedure was translated to a canning procedure, modifications had to be done specifically, conducting a partial precooking of the product before processing to reduce the effect of overcooking. The modified procedure when subjected to heat penetration studies to establish the thermal process schedule was computed to be 41 ± 2 minutes at 121.1°C using Clostridium sporogenes PA 3679 as the reference organism. The calculated process was verified using cut-out tests, physico-chemical tests, microbiological examination, and sensory evaluation. Results showed that the calculated process was enough to produce a commercially sterile and acceptable canned Everlasting, packed in 300 x 200 cans with a fill-in-weight of 170 ± 5 grams. Further improvements in the canned Everlasting are recommended to obtain a product that can be successfully marketed locally and internationally